Abusive relationships in the light of scheme therapy: a systematic review (Research, Society and Development, 2022)
Violence against women is considered to be any violent act that has its justification in gender and has the possibility of causing physical, sexual and/or psychological harm, including the threat, coercion or deprivation of liberty in a private or public environment. That said, this study aims to carry out a systematic review of the literature, gathering the main articles found in 4 (four) databases - SciELO, Scopus, MEDLINE/PubMed and the American Psychological Association (APA) - that study violence against women in abusive relationships and, in view of this, to elucidate how Schema Therapy can contribute to clarifying the occurrence of women's permanence in these relationships. This is a documentary study of a descriptive, exploratory and qualitative nature. The search was carried out over a period of ten years, from January 1, 2011 to December 31, 2021. For the selection of articles, the search terms (TS) “Pandemic and covid and violence or abuse and relationship” were used. Based on the defined criteria, 47 publications were obtained in Portuguese and English, however only 22 articles were included in the systematic review study, being 7 qualitative studies and 15 of a quantitative-qualitative nature. These studies highlight the theme of domestic violence and cyber violence, which were related to the EID's of subjugation, emotional deprivation, negativity, social isolation/alienation and abandonment, as well as the aggravation of these situations as a result of the pandemic context of covid-19.